What is quality 4.0? A review of the literature - Hernández Chávez, Gerardo (2024)
The objective of the present research is to conduct a systematic literature review on the conceptual definition of Quality 4.0, the elements of Quality 4.0, the skills needed by employees for Quality 4.0, and the barriers that companies have been facing for the implementation of Quality 4.0. Fifty articles obtained from Scopus and Google Scholar were collected and reviewed over a period from 2017 to 2023. First, a descriptive analysis was performed according to the year of publication and publication sources. Next, the selected articles were classified according to the four research topics. This research contributes to the quality literature in which professionals, managers, entrepreneurs and researchers can understand and apply Quality 4.0 in order to improve the productivity and competitiveness of organizations.